TRAJECTORIES OF EDUCATION POLICY-MAKING IN GHANA: EXPLORING THE JOURNEY TO DEPOLITICISATION PROCESS - Mohammed Gunu, Ibrahim Mohammed (Advances in Social Sciences Research Journal, 2019)
This paper examines education policy-making in Ghana. It focuses on the roles different policy actors should play to depoliticise the process of education policy-making. The depoliticisation agenda as contains in this presentation has the potential to promote Sustainable National Development. This paper examines how far key actors like political parties and academics matter in the depoliticisation of education policy issues in Ghana. Drawing on Foucault discourse theory, past and present education policy-making processes are examined through a review of documents and literature. The analyses show that the current education policy-making procedure in Ghana is largely dependent on the ruling party manifesto and through committees or commissions set-up by the ruling governments to determine educational policy issues. The educational policies as contained in the ruling party manifesto and committees or commissions reports are reproduced in national legislation by the government. These legislative arrangements often receive the endorsement of the majority in parliament and in the fourth republic, for now, the ruling party is always in majority. The partisan politics associated with these processes are largely responsible for the politicisation process. Overall, this paper argues that evidence-based policy and practice can potentially reduce partisan politics in education policy-making in Ghana.